Acute-on-chronic liver failure following eribulin treatment for metastatic breast cancer: a case report. Issue 7 (July 2022) - Xie, Xiao-Feng; Huang, Jia-Yi; Chen, Li-Ping; Lan, Xiao-Feng; Zhang, Qiu-Yi; Song, Lin; Bai, Xue-; Du, Cai-Wen
The efficacy and tolerability of eribulin mesylate, a synthetic halichondrin B analog, in patients with metastatic breast cancer (MBC) previously treated with anthracyclines and taxanes have been established. Acute-on-chronic liver failure (ACLF) is a clinical syndrome manifesting as acute and severe hepatic derangement resulting from varied insults in patients with established chronic liver disease or cirrhosis who did not previously receive eribulin. A middle-aged woman diagnosed with MBC and diffuse liver metastases who was pretreated with multi-line chemotherapy received eribulin as eighth-line chemotherapy and presented with hepatic encephalopathy, rapid bilirubin elevation, and significant coagulation dysfunction on day 4 in cycle 1. The patient was diagnosed with ACLF induced by eribulin. Therefore, ACLF may be a lethal and rare adverse event when patients with chronic liver metastases receive eribulin treatment, and clinicians' awareness should be increased for optimal prevention and prompt diagnosis and treatment.